SEMANTIC HIERARCHIES IN BIOTECHNOLOGY TERMINOLOGY: A STUDY OF HYPER-HYPONYMIC RELATIONS IN ENGLISH AND UZBEK - Adambaeva Feruza Rustambekovna (Modern American Journals, 2025)
This article explores hyper-hyponymic relations as one of the core paradigmatic structures in biotechnology terminology. Drawing on theoretical insights from linguistics and terminology studies, it classifies various semantic relationships such as general–specific concepts, class–member, parameter–carrier, process–object, and property–object. Examples from both English and Uzbek demonstrate how these hierarchical relations organize and clarify scientific knowledge. The study reveals that biotechnology terminology forms multi-level, intersecting taxonomies, where a term may function as a hyponym in one context and a hypernym in another. The findings contribute to a deeper understanding of systematicity in specialized language and provide a linguistic basis for more effective terminology development, translation, and interdisciplinary communication.
Keywords: Terminology, hyponymy, biotechnology, systematicity, taxonomy, semantics, hyper-hyponymic relations, semantic hierarchy